(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
Hydatid cyst is a zoonotic disease caused by the larval stage of the worm Echinococcus granulosus. The study aimed to isolate and identification of bacteria associated the fluid of hydatid cysts isolated from the livers of cattle and sheep. 75 samples were collected from the liver of sheep and cattle infected with hydatid cysts during the period from February 2022 to March 2022 from South Iraq. The diagnosis was made using phenotypic and biochemical methods, where the percentage of infection with bacteria associated with hydatid cyst fluid isolated from sheep liver was 100%, while the percentage of infection with bacteria associated with hydatid cysts in cows liver was 88%, the results of biochemical tests were of bacteria Escherichia coli, Shigella spp, Proteus spp, Providencia spp, Klebsiella spp. To confirm the validity of the test, it was diagnosed using the Vitekll technique. Seven sample isolated from cattle liver were diagnosed, two of which were diagnosed for sheep liver and one for cow liver, and 4 isolates could not be identified, so the results of sheep isolates were Staphylococcus lents, Aeromonas sobria, Where it was inconsistent with the biochemical diagnosis, its biochemical diagnosis was Shigella spp, E.coli. As for the cow isolate, it was Kocuria kristinae, and the result was that there was no compatibility between it and the biochemical diagnosis. As for the antibiotic sensitivity test, where the isolates were more sensitive to antibiotics Vital Gentamicin , Ceftazidim , Cefepim Imipenem , Ciprofloxacin , Amikain , Trimethoprim / sulfamethoxazole , Piperacillin / Taz obactam, Ticarcillin/Clavulanic, Ticarcillin, Ticarcillin/clavulanic acid, Ticarcillin, Imipenem. Therefore, we conclude that the percentage of bacteria associated with sheep livers is higher than the percentage of bacteria in cows, and that negative bacteria are the most present for hydatid fluid bacteria.